(untitled) (Journal of Green Business School, 2025)
Confusion that remains regarding the concept, time path, and impacts of globalization are addressed in the paper. Globalization involving cross-border exchanges of goods, capital, technology, and ideas has existed since the Old Ages. The pace of the process surged in the post-World War II era and got a further fillip in the 1980s when many countries in Africa and Asia, including Bangladesh and its neighboring countries like India and China, took it up more seriously. Globalization is changing the mix of international exchanges: services, manufactures, and intra-industry trade are assuming ever-increasing importance. Globalization is a win-win game for countries going for it with commensurate reforms with a check and balance approach. J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 41-52